2013
DOI: 10.1186/1556-276x-8-504
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hole shape/size on the growth of site-selective quantum dots

Abstract: The number of quantum dots which nucleate at a certain place has to be controllable for device integration. It was shown that the number of quantum dots per nucleation site depends on the size of the hole in the substrate, but other dimensions of the nucleation site are vague. We report on the influence of hole shape on site-selectively grown InAs quantum dots (QDs) by molecular beam epitaxy. Dry etching of the GaAs wafers was used because of its high anisotropic etching characteristic. Therefore, it was possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Table 1 shows a comparison between the nanohole depths used for the site-controlled growth of InAs QDs on GaAs. A range of techniques are In this study, we observed a low standard deviation (SD) in nanohole radius and depth which is an encouraging result for reducing inhomogeneity in site-controlled QD size, emission wavelength and occupancy [27,28]. The SD in radius was between 15 and 3 nm, with no trend seen when increasing voltage or humidity.…”
Section: Resultssupporting
confidence: 51%
“…Table 1 shows a comparison between the nanohole depths used for the site-controlled growth of InAs QDs on GaAs. A range of techniques are In this study, we observed a low standard deviation (SD) in nanohole radius and depth which is an encouraging result for reducing inhomogeneity in site-controlled QD size, emission wavelength and occupancy [27,28]. The SD in radius was between 15 and 3 nm, with no trend seen when increasing voltage or humidity.…”
Section: Resultssupporting
confidence: 51%
“…As the actual shape of pits does influence the energy of the system and, more in general, island nucleation [ 26 , 27 ], it is crucial to control their morphology. This is not trivial: after all, pits are just holes drilled into the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…In molecular beam epitaxy (MBE) processes, this can be achieved by defining the nucleation sites for impinging atoms using patterning the surface. Patterning is usually accomplished by lithographic techniques, such e-beam lithography [7][8][9][10][11], nanoimprint lithography [12], interference lithography, photolithography [13], or atomic force microscopy (AFM) lithography [14].…”
Section: Introductionmentioning
confidence: 99%